Internship and Entrepreneurship in computer science - Alfan, Muhammad Bahauddin; Sangjaya, Sabri; Rusdiansyah, Muhammad Rizal; Arfabuma, Fandi M; Kurubacak, Gulsun (Association for Scientific Computing Electrical and Engineering, 2023)
Graduated students of State University of Malang majoring in Computer Science have required to do an internship in industry. Generally, the chosen private industry is in the form of a startup such as learning media applications and games. In this case, the authors would like to conduct research related to the impact of an internship program and another Computer Science subject related to entrepreneurial skills. It is expected that this research can improve the quality of student graduates in order to have an entrepreneurial spirit.